2007
DOI: 10.1007/s10620-007-9930-1
|View full text |Cite
|
Sign up to set email alerts
|

A Survey about Irritable Bowel Syndrome in South Korea

Abstract: The aims of the present study were: (1) to assess the prevalence of symptom-based irritable bowel syndrome (IBS) in Korean adults, (2) to assess several organic abnormalities which can be found in IBS patients, and (3) to analyze the risk or associated factors that influence the presence of IBS. Adult health examinees were requested to fill out a questionnaire. The prevalence of IBS was calculated using Rome II criteria. Using several tests, several organic abnormalities were identified in the IBS group. Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In our previous study, conducted in 42 IBS patients diagnosed by the Rome Ⅱ criteria, the microscopic findings of mucosal hyperplasia, lymphocyte aggregation, and increased eosinophil counts were more frequently observed in the IBS group than the control group. Microscopic colitis does not appear to be associated with IBS symptoms [62] . A study in Malaysia also identified microscopic inflammations in D-IBS subjects that did not meet the criteria for classical microscopic colitis.…”
Section: Inflammationmentioning
confidence: 81%
“…In our previous study, conducted in 42 IBS patients diagnosed by the Rome Ⅱ criteria, the microscopic findings of mucosal hyperplasia, lymphocyte aggregation, and increased eosinophil counts were more frequently observed in the IBS group than the control group. Microscopic colitis does not appear to be associated with IBS symptoms [62] . A study in Malaysia also identified microscopic inflammations in D-IBS subjects that did not meet the criteria for classical microscopic colitis.…”
Section: Inflammationmentioning
confidence: 81%
“…Many studies have assessed that the overall prevalence of IBS as up to approximately 25% using the Manning and the Rome criteria worldwide 12,21,22. To date, the prevalence of IBS in Korea using the Rome II criteria has been estimated as ranging from 6.6% to 16.8% 23,24. Many studies about diagnostic criteria for IBS have been performed since the publication of the Rome III criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies about diagnostic criteria for IBS have been performed since the publication of the Rome III criteria. However, there are few studies regarding the prevalence of IBS diagnosed by the Rome II criteria in Asian countries,23,24 and the Rome III criteria have only recently been published to diagnose and classify IBS. Moreover, only a few studies have compared the Rome II and III criteria for IBS, worldwide 8,18…”
Section: Introductionmentioning
confidence: 99%
“…In United States, IBS is known as the most common gastrointestinal disease and comprises 25 to 50% of all referrals to gastroenterologists,1 and the prevalence of IBS has estimated to range 9% to 22% of the population 2. In Korea, Park et al3 reported the prevalence of IBS increased up to 16.8%. A few effective medicines such as cisapride, tegaserod and alosetron have been withdrawn from the market because of their serious adverse drug reactions.…”
Section: Introductionmentioning
confidence: 99%